Bicuspid aortic valve repair—current techniques, outcomes, challenges, and future perspectives - Zhang, Haiyu (Frontiers in Cardiovascular Medicine, 2024)
Bicuspid aortic valve (BAV) is a common congenital heart condition that can lead to some valve-related complications, such as aortic stenosis and/or regurgitation, and is often associated with aortic root dilation. With the development and refinement of BAV repair techniques over the past three decades, surgical repair of BAV has emerged as an effective treatment option, offering symptomatic relief and improved outcomes. This review aims to summarize the current techniques, outcomes, and challenges of BAV repair, and to provide potential future perspectives in the field.